2019
DOI: 10.3390/app9091872
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Background Sounds on Annoyance Reaction to Foreground Sounds in Psychoacoustic Experiments in the Laboratory: Limits and Consequences

Abstract: In a variety of applications, e.g., psychoacoustic experiments, virtual sound propagation demonstration, or synthesized noise production, noise samples are played back in laboratories. To simulate realistic scenes or to mask unwanted background sounds, it is sometimes preferable to add background ambient sounds to the noise. However, this can influence noise perception. It should be ensured that either background sounds do not affect, e.g., annoyance from foreground noise or that possible effects can be quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…It is reasonable to assume that higher (or cumulative) sound pressure levels are generally associated with lower acoustic comfort ratings (see Section 5.6 for a discussion on the effect of sound pressure level on acoustic comfort). This is consistent with other laboratory experiments, whereby "short-term noise annoyance" was reported either not to be significantly affected by increasing playback sequence or to increase with it (Schäffer et al, 2016(Schäffer et al, , 2019Taghipour and Pelizzari, 2019;Taghipour et al, 2019a). Hereby, it is noted that increased noise annoyance is typically associated with decreased acoustic comfort (Yang and Kang, 2005).…”
Section: Discussion and Implications Of The Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…It is reasonable to assume that higher (or cumulative) sound pressure levels are generally associated with lower acoustic comfort ratings (see Section 5.6 for a discussion on the effect of sound pressure level on acoustic comfort). This is consistent with other laboratory experiments, whereby "short-term noise annoyance" was reported either not to be significantly affected by increasing playback sequence or to increase with it (Schäffer et al, 2016(Schäffer et al, , 2019Taghipour and Pelizzari, 2019;Taghipour et al, 2019a). Hereby, it is noted that increased noise annoyance is typically associated with decreased acoustic comfort (Yang and Kang, 2005).…”
Section: Discussion and Implications Of The Resultssupporting
confidence: 91%
“…While almost all sounds yielded a negative rating concerning the perceived acoustic comfort, relatively pleasant and relatively unpleasant sounds were found to increase and decrease acoustic comfort, respectively. Enabling facilities that invite relatively pleasant sounds, e.g., playing children as well as water features, birds and vegetation (Jeon et al, 2010;De Coensel et al, 2011;Taghipour and Pelizzari, 2019) and avoiding facilities which encourage relatively unpleasant sounds and noisy activities (such as basketball) might improve the overall acoustic comfort in inner yards. This point should be, however, treated with caution, due to inherent differences between shortterm responses in a laboratory setup and long-term effects of the sounds in a living environment (Schäffer et al, 2016;Taghipour et al, 2019a).…”
Section: Discussion and Implications Of The Resultsmentioning
confidence: 99%
“…Introducing additional background sounds in the noise-polluted sound environment would lead to even higher SPL. Despite that, certain background sounds seem to have a positive influence on the perception of the soundscape [49][50][51][52][53][54]. Relatively pleasant background sounds are shown to be associated with increased acoustic comfort [10] and decreased noise annoyance [54].…”
Section: Background Soundsmentioning
confidence: 99%
“…Despite that, certain background sounds seem to have a positive influence on the perception of the soundscape [49][50][51][52][53][54]. Relatively pleasant background sounds are shown to be associated with increased acoustic comfort [10] and decreased noise annoyance [54]. More specifically, it has been suggested that sounds of water features, birds, or natural vegetation could improve the quality of the (acoustic) living environment [51,52].…”
Section: Background Soundsmentioning
confidence: 99%
“…This separation of foreground events from background noise has subsequently been widely used (e.g. [17][18][19][20]).…”
Section: Environmental Sound and Headphone Media Parametersmentioning
confidence: 99%